2000
DOI: 10.1068/p2352
|View full text |Cite
|
Sign up to set email alerts
|

An Oblique Effect in Aesthetics: Homage to Mondrian (1872–1944)

Abstract: The effect of the orientation of Mondrian's paintings on their aesthetic appeal was examined. Eight paintings, four with horizontal/vertical frames in the original and four with oblique frames, were presented in eight different orientations and rated for aesthetic appeal on a 7-point scale. There was a stronger preference for pictures presented so that their component lines were horizontal and vertical than for pictures presented with their component lines in an oblique orientation. In addition, subjects showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
79
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 20 publications
16
79
1
Order By: Relevance
“…So artists tend to use more horizontal and vertical lines than oblique in their compositions. The extreme example of this is Mondrian, and we have shown that, independently of frame orientation, Mondrian's paintings are preferred when their component lines are horizontal and vertical (Latto, Brain, & Kelly, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So artists tend to use more horizontal and vertical lines than oblique in their compositions. The extreme example of this is Mondrian, and we have shown that, independently of frame orientation, Mondrian's paintings are preferred when their component lines are horizontal and vertical (Latto, Brain, & Kelly, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed he felt so strongly about this that when in 1932 van Doesburg, another founding member of the De Stijl group of painters, insisted on using diagonals, he broke off his connection with the group (Jaffé, 1970). We have shown that Mondrian was correct in his judgment: paintings composed of horizontal and vertical lines are preferred to those composed of oblique lines, even if frame orientation is controlled for (Latto, Brain, & Kelly, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Extensive work on human visual preferences shows that humans prefer cardinal to oblique lines (Latto, Brain, & Kelly, 2000), and curved to sharp forms (Bar & Neta, 2006). Miura and colleagues (2010) showed how smooth and fluent dance movements were preferred over awkward ones (Miura, Sugiura, Takahashi, Sassa, Miyamoto, Sato, et al, 2010).…”
Section: Symmetry Synchronization Lines and Astonishing Solosmentioning
confidence: 99%
“…The psychophysical 'oblique effect', first named by Stuart Appelle (1972), is the principle that "our perception of oblique or diagonal lines is slightly inferior to our perception of horizontal and vertical lines" (Latto et al, 2000). Perhaps the earliest mention of the oblique effect in the vision literature was cited by Mach (1861) who found that observers were more accurate at matching a line parallel to a horizontal or vertical comparison line than to an oblique line (Mach 1861, cited in Westheimer 2003.…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractObservers prefer paintings by Piet Mondrian in their original orientation compared to when rotated -"The Oblique Effect" (Latto et al, 2000). We tested whether eye movements could provide any insight into this aesthetic bias.
…”
mentioning
confidence: 99%